Diving Deeper to The State Administrator Asset Report (Laporan Harta Kekayaan Pejabat Negara - LHKPN): From Public Perception to Data Analytics - Putra, Yonna Ribut Perdana; Soeharto, Indra (Association of Certified Fraud Examiners Indonesia Chapter, 2024)
This research aims to portray public perceptions towards The State Administrator Asset Report - Laporan Harta Kekayaan Pejabat Negara (LHKPN) as one of the corruption eradication tools. Further, it summarizes public perception on the LHKPN’s information quality and its effectiveness. In selecting the respondents, this research applies purposive sampling technique. Respondents of this research are individuals aged over 26 years old who live in 3 cities, namely: Jakarta, Surabaya, and Makassar. This research concludes that the public has concerns regarding the quality of data reported into the LHKPN. Public also negatively perceive the effectiveness of the LHKPN’s as a tool for eradicating corruption in Indonesia. To improve such a situation, it is proposed to use digital technologies (e.g., data analytics, big data) to perform detailed analysis on the information contained in the LHKPN. Such a measure is expected to be able to detect any possible red flags. The research also noted that the involvement of civil society to monitor the LHKPN is encouraged.